Intervention Capacity Analysis Health Promotion Of Non-Communicable Diseases In Tasikmalaya City - Maulana, Heri DJamiatul; Peni Cahyati; Dudi Hartono; Sri Mulyanti (Poltekkes Kemenkes Tasikmalaya, 2025)
Non-communicable diseases (NCDs) are one of the leading causes of death in Indonesia, including in Tasikmalaya city, with an increasing prevalence. This study aims to analyze the capacity of health promotion interventions in the prevention and control of NCDs in Tasikmalaya city. The methodology used was a cross-sectional survey involving 31 health promotion program managers at puskesmas. Data were collected through a 2010 WHO capacity mapping instrument questionnaire, with eight domains of health promotion capacity. The results showed that the average capacity of health promotion interventions was at developmental level C, meaning that the program had begun to be implemented, but its impact could not yet be clearly assessed. There was a significant shortfall in the number of human resources trained specifically for NCD health promotion, as well as low budget allocations. The variation in respondents' ratings suggests the need for better evaluation and monitoring of the program's effectiveness. Based on these findings, the study recommends improving HR training, developing more targeted policies, increasing financing, and strengthening collaboration with various stakeholders. With these measures, it is hoped that efforts to prevent and control NCDs in Tasikmalaya City can be more effective and sustainable, thereby reducing the burden of disease in the community.